High-yield Exfoliation of Graphite in Acrylate Polymers: A stable few-layer graphene nanofluid with enhanced thermal conductivity - Sun, Zhenyu; Pöller, Sascha; Masa, Justus; Kilzer, Andreas (Carbon, 2013)
High-yield exfoliation of pristine graphite in low boiling point alcohols was achieved using a set of acrylate polymers resulting in few-layer graphene concentrations of up to ∼4 mg mL−1. The polymer showed superior dispersing capabilities for graphene compared to the best reported dispersants, including the solvent N-methyl-pyrrolidone, the surfactants sodium cholate and sodium taurodeoxycholate, and the polymer polyvinylpyrrolidone. The dispersions were stable regardless of freezing (−26 °C) or heating (70 °C) for 24 h, or dilution with water up to 80% volume ratio over 160 h. The as-obtained nanofluid exhibited an enhancement in thermal conductivity suggesting a great potential in coolant applications.